Gauged system mımıckıng the gürsey model - Hortacsu, M.; Luetfueoglu, B. C.; Taskin, F. (World Scientific Pub Co Pte Lt, 2007)
We comment on the changes in the constrained model studied earlier when constituent massless vector fields are introduced. The new model acts like a gauge-Higgs–Yukawa system, although its origin is different.
Keywords: High Energy Physics - Theory; gauged constrained models higher order processes; High Energy Physics - Theory (hep-th); Nuclear physics; FOS: Physical sciences; Strong interaction, including quantum chromodynamics